PID PATH FOLLOWING CONTROL SYSTEM DESIGN ON UNMANNED AUTONOMOUS FORKLIFT PROTOTYPE - Herlambang, Teguh; Indriawati, Katherin; Akbar, Reza Maliki; Nurhadi, Hendro (PATTIMURA UNIVERSITY, 2024)
One of the technologies often used in material handling and material transport is forklift. Conventionally forklifts are operated by human operators. For efficiency, to improve security, safety, and occupational health and to minimize the risk of operators, forklifts can be automated. Therefore, the idea of unmanned autonomous forklift innovation was introduced. In this final project, a motion control system was designed for an unmanned autonomous forklift prototype both in simulation and hardware using PID control techniques, and the odometry system was equipped with a rotary encoder. In the simulation, the controlled variable was the distance and the manipulated variable was the force on the vehicle. Meanwhile, in the prototype, the controlled variable was distance and the manipulated variable was the motor pulse. In the simulation stage the PID control parameters were applied . with an error of 0.32% in the simulation. The PID control parameters were applied to the prototype, that is, . The distance tests were done with variation of 50 cm to 200 cm (25 cm intervals). One variation of the distance experiment was done 5 times. The average absolute error resulted was 2.36 cm.